Multiancestry genome-wide association study of 520,000 subjects identifies 32 loci associated with stroke and stroke subtypes - Chauhan, Ganesh; Traylor, Matthew; Sargurupremraj, Muralidharan; Okada, Yukinori; Mishra, Aniket; Giese, Anne-Katrin; van der Laan, Sander W.; Gretarsdottir, Solveig; Anderson, Christopher D.; Almgren, Peter; Amouyel, Philippe; Bartz, Traci M.; et al. (Nature genetics, 2018)
Stroke has multiple etiologies, but the underlying genes and pathways are largely unknown. We conducted a multiancestry genome-wide-association meta-analysis in 521,612 individuals (67,162 cases and 454,450 controls) and discovered 22 new stroke risk loci, bringing the total to 32. We further found shared genetic variation with related vascular traits, including blood pressure, cardiac traits, and venous thromboembolism, at individual loci ( n = 18), and using genetic risk scores and linkage-disequilibrium-score regression. Several loci exhibited distinct association and pleiotropy patterns for etiological stroke subtypes. Eleven new susceptibility loci indicate mechanisms not previously implicated in stroke pathophysiology, with prioritization of risk variants and genes accomplished through bioinformatics analyses using extensive functional datasets. Stroke risk loci were significantly enriched in drug targets for antithrombotic therapy. Multiancestry genome-wide association analyses identify new risk loci for stroke and stroke subtypes. Fine mapping and bioinformatics analyses of these risk loci point to mechanisms not previously implicated in stroke pathophysiology.